2018
DOI: 10.1111/head.13423
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Status in a Group of Migraine Patients Compared With Healthy Controls: A Case–Control Study

Abstract: Objective The association between serum vitamin D and migraine is investigated in this research.s Background Although the pathogenesis of migraine headache is not fully understood, the possible role of inflammation and disturbed immune system has been proposed; thus, higher levels of vitamin D might reduce the risk of migraine. However, the results of related studies have been inconclusive. Methods Seventy healthy individuals and 70 age‐ and sex‐matched migraineurs (34 chronic and 36 episodic migraineurs), dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
3
32
2
2
Order By: Relevance
“…[30][31][32][33] Furthermore, there is a considerable body of literature on decreased magnesium levels especially during ictal phases in migraine suffers when comparing to healthy individuals. In the current study, it was shown that increasing levels of serum B12 by more than 643 pg/mL was accompanied by roughly 80% decrease in the odds of having migraine after considering age, gender, BMI, and for taking NSAIDs and anticonvulsant drugs in the fully adjusted multiple regression model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[30][31][32][33] Furthermore, there is a considerable body of literature on decreased magnesium levels especially during ictal phases in migraine suffers when comparing to healthy individuals. In the current study, it was shown that increasing levels of serum B12 by more than 643 pg/mL was accompanied by roughly 80% decrease in the odds of having migraine after considering age, gender, BMI, and for taking NSAIDs and anticonvulsant drugs in the fully adjusted multiple regression model.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between other nutrient insufficiencies or deficiencies and migraine, evidence showed that migraineurs may suffer from lower levels of 25(OH)D the main biomarker of vitamin D status, in comparison with healthy controls. [30][31][32][33] Furthermore, there is a considerable body of literature on decreased magnesium levels especially during ictal phases in migraine suffers when comparing to healthy individuals. [34][35][36] Moreover, it has been demonstrated that supplementation with vitamin B2, 37-40 B9, B6, [41][42][43][44][45] vitamin D, [46][47][48] and magnesium [49][50][51] could attenuate migraine features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies revealed vitamin D deficiency or insufficiency in migraine patients, while some other studies showed normal vitamin D level (levels ranging from 12.40 to 38.08 ng/mL) [53,65]. Although some studies found no differences in vitamin D levels between the migraine and control groups [49,53,66], others found significant differences [54,55,65]. In particular, Togha et al reported a higher serum vitamin D level (i.e., between 50 and 100 ng/mL) was associated with 80-83% lower odds of migraine headaches than those with serum levels below 20 ng/mL, after considering several confounding variables (including gender, age, and body mass index) [55].…”
Section: The Role Of Vitamin D In Migrainementioning
confidence: 99%